PEMANFAATAN TANAH ASET PT KERETA API INDONESIA (PERSERO) DIVISI REGIONAL II SUMATERA BARAT OLEH PIHAK KETIGA - Nasrul, Oky (Soumatera Law Review, 2019)
Utilization of land assets of PT. KAI, shich aims to develop the potential and support of railway business activities. In fact today, there are many land utilization of PT. KAI is used for activities outside the railway. Therefore, a proper and ideal policy is needed, in order to achieve the land use in accordance with the prevailng land law. This study discusses the form and implementation of land assets pf PT. KAI by a third party and the legal validity of the consideration of PT. KAI provides the use of land for activities outside the railway. This paper is expected to contribute thoughts and PT. KAI guidelines in implementing the utilization of its asset land. This research is a legal research with empirical juridical research method, descriptive analysis research spesification. Data collection methods and techniques gained from primary data and secondary data. Methods of data analysis used the method of qualitative analysis.The conclusion in this research is the form of utilization of asset land by third party is, Buil Operate an Transfer (BOT), Buid Transfer and Operate (BTO), Joint Operation, Business Cooperation, Lease, Borrow.Utilization of asset land implemented by PT. KAI is by means of Lease and Giving of HGB above HPL. The reason for the utilization of land asset of PT. KAI beyond supporting business activities to optimize all existing assets, so that PT. KAI benefits and income from these lands. Utilization of land assets of PT. KAI outside railway activities is contrary to Article 44 of UUPA and is not accordance with the regulation of Directors of PT. KAI No. 023-VII/KAI/Dir.II/2002 so resulting in the act being null and void or considered to be non-existent.